Fabrication and bending property of fiber metal laminates using nanofillers modified epoxy resins - Heung, Cheuk Hei. (2011)
This report documented the year long Final Year Project programme done by the student from July 2010 to May 2011. With the help of detailed diagrams, graphs, literature review, etc, this report gives an insight into the project student undertakes. This project is about the bending properties of different combination of fibre metal laminates using different type of fibre and modified epoxy. It begins with an introduction of this project and an overview of fibre metal laminate.